COVID-19 and Food Safety FAQ: Is Coronavirus an Issue in Produce Production? - Natalie Seymour; Mary Yavelak; Candice Christian; Ben Chapman; Michelle Danyluk (EDIS)
CDC, FDA and USDA have no reports at this time of human illnesses that suggest coronavirus can be transmitted by food or food packaging. Research on similar viruses, such as SARS and influenza, show risk of transmission from food is very low. While information on if or how long virus persists on surfaces is minimal, risk of foodborne transmission is low and should not be of concern. This flyer, written by Natalie Seymour, Mary Yavelak, Candice Christian, and Ben Chapman (NC State University Extension), provides answers to some frequently asked questions about coronavirus and produce production. Published by the UF/IFAS Food Science and Human Nutrition Department, March 2020.